Promoting Nutrition in Climate Smart Agriculture - Itliong, Kirstein; Valdemoro, Camille; Calica, Michelle Jeanne; Barbon, Wilson John; Myae, Chan; Su, Myat Noe; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This booklet resulted from the project titled, “Community Based Adaptation via Climate and nutrition smart village to address food insecurity in Myanmar. The project aimed to contribute to food and nutrition security, food safety and hygiene in the communities where the project beneficiaries live. Drawing from the project’s experiences and lessons, the booklet serves as a guide for enhancing food production, food safety and hygiene beginning from the smallest unit of the community – the family.